Study of intravenous ferric carboxy maltose in iron deficiency anemia in women attending gynecological clinic - safety and efficacy - Mishra, Vineet V.; Dharaiya, Nisarg; Aggarwal, Rohina; Choudhary, Sumesh; Gandhi, Khushali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Several intravenous iron preparations are available for the treatment of iron deficiency anemia (IDA). Some of these require multiple small infusions to prevent labile iron reactions while iron dextran (DEX) is associated with a risk of potentially serious anaphylactic reactions. Ferric carboxymaltose (FCM), a nondextran intravenous iron, is an effective and a safe option which can be administered in high single doses without serious adverse effects. Methods: It was a prospective study including 150 women of age >18 years with a definitive diagnosis of IDA and Hemoglobin (Hb) between 7-10 gm% from December 2013 to October 2014.Out of these, eleven women were lost to follow up and were excluded from the study. Intravenous FCM (500-1000mg) was administered and the improvement in Hb levels and iron stores was assessed after 3 weeks of total dose infusion. Results: Out of 150, 139 women were included in the study. Most of the women were in the age group of 30-39 years (38.12%). Most of the patients (74.10%) had mild anemia. Mean Hb levels increased over a period of 3 weeks after FCM administration from 8.70±1.04 gm% to 11.07±1.02 gm% which was statistically significant. Other parameters like S.TIBC (Serum total iron binding capacity), S. Ferritin, S. Iron also suggested a significant improvement after FCM administration. No serious life threatening adverse events were observed with FCM. Conclusion: Intravenous FCM is an effective and a safe treatment option for IDA and has an advantage of single administration of high doses without serious adverse effects.